Fluoxetine Induced Hair Loss: A Case Report - Mermi, Osman; Atmaca, Murad; Kilic, Faruk; Gurok, M. Gurkan; Kuloglu, Murat (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2014)
Hair loss is a frequent adverse effect that may occur by psychotropic drug use and that can remit by its cessation. Some side effects such as skin rush, urticaria, and skin eruptions induced by Selective Serotonin Re-uptake Inhibitors (SSRIs) may be observed. In addition to these dermatologic side effects, hair loss extending to alopecia has been reported. In this paper, we report a case of fluoxetine-induced pervasive hair loss recovering after its discontinuation.
Keywords: Fluoxetine; hair loss; side effect